2015
DOI: 10.1021/acs.chemmater.5b02092
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Sodium-Ordered Form of Na3V2(PO4)3 below Ambient Temperature

Abstract: The crystal structure of the NASICON Na3V2(PO4)3 phase (NVP) has been investigated as a function of temperature. Combining laboratory and synchrotron X-ray powder diffraction with single crystal X-ray diffraction, we demonstrate the presence of four polymorphs of NVP from 30 to 225 °C. While the high temperature γ-NVP crystallizes in the classical rhombohedral cell (S.G. R3̅c, a = 8.73382(4) Å, c = 21.91438(17) Å), the low temperature α-NVP undergoes a monoclinic distortion (S.G. C2/c, a = 15.1244(6) Å, b = 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
167
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(188 citation statements)
references
References 19 publications
16
167
3
2
Order By: Relevance
“…1 Electrochemical signatures of Na 3 V 2 (PO 4 ) 3 electrodes upon Na + extraction (left) or Na + insertion (right). 15,31 Order-disorder transitions within the Na + sub-lattice are typical of NAtrium Super Ionic CONductors (NASICON) and are associated with a randomization of the Na + positions and a lowering of the activation energy for ionic conduction. 15,17 This leads to a set of superstructure diffraction peaks, indicated in Fig.…”
Section: Results and Discussion A Structural Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Electrochemical signatures of Na 3 V 2 (PO 4 ) 3 electrodes upon Na + extraction (left) or Na + insertion (right). 15,31 Order-disorder transitions within the Na + sub-lattice are typical of NAtrium Super Ionic CONductors (NASICON) and are associated with a randomization of the Na + positions and a lowering of the activation energy for ionic conduction. 15,17 This leads to a set of superstructure diffraction peaks, indicated in Fig.…”
Section: Results and Discussion A Structural Considerationsmentioning
confidence: 99%
“…Minor "impurities" refer to traces of V 2 O 3 or to the incommensurate form of NVP (see31 ). The "new" diffraction peaks ($) refer to d hkl values not indexable in the rhombohedral R 3c space group.…”
mentioning
confidence: 99%
“…13 Also with the enlarged monoclinic cell, recently suggested by Chotard et al for NVP, it is not possible to index all observed Bragg peaks. 3 The comparison of their reconstructed reciprocal space layer 0 kl with those of this study reveals substantial differences with the superstructure peaks appearing along the c * direction; for NVP, they appeared along the b * direction. The only possibility to index all Bragg peaks for NSP fit with a 2 a , 2 b , c trigonal cell.…”
Section: Resultsmentioning
confidence: 61%
“…As an example, in the case of Na 3 V 2 (PO 4 ) 3 (NVP) a phase transition sequence from an ordered monoclinic α form (space group (SG) C2/ c , a = 15.1244(6) Å, b = 8.7287(3) Å, c = 21.6143(8) Å, β = 90.163(2)) to the classical disordered rhombohedral cell ( SG R 3̅ c , a = 8.73382(4) Å, c = 21.91438(17) Å) with two intermediate incommensurate modulated structures β and β′ was described. 3 A further complication arises due to the different and conflicting behavior of powders and single crystals of NASICON-materials. 4 For polycrystalline samples of Na 3 Sc 2 (PO 4 ) 3 (NSP), fabricated at high temperatures, two phase transitions are reported 57 with the room temperature (RT) structure often being described using a monoclinic cell with space group symmetry C 2/ c .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many commensurately or incommensurately modulated compounds with intriguing structure and physical properties have been reported. [8][9][10] Rare-earth phosphates with the general formula Ln(PO 3 ) 3 (Ln=Sc, Y, La− Lu) are one of the most attractive family mainly for their optical applications. [11][12][13] Their good chemical and thermal stability as well as relatively simple preparation ensure their wide application in many fields.…”
Section: Introductionmentioning
confidence: 99%